Alterations in the basal ganglia in patients with brain tumours may be due to excessive iron deposition - Herynek, Vít; Wagnerová, Dita; Malucelli, Alberto; Vymazal, Josef; Sameš, Martin; Hájek, Milan (Oncology letters, 2015)
The accumulation of iron in the brain is a common physiological process. However, alterations in the deposition of iron or other paramagnetic substances are associated with various diseases. In the present study, the deposition of paramagnetic substances in patients with brain tumours was evaluated using T2 relaxometry. A total of 23 patients with untreated tumours or with recurrent tumours following treatment, together with a group of 19 age-matched healthy controls, were examined using T2 relaxometry at 3T. The relaxation times in the basal ganglia, thalamus and white matter were evaluated. Significantly lower T2 relaxation times were identified in the basal ganglia and thalamus of the patients with tumours, as compared with those of the controls (P<0.05). No statistically significant difference was identified between patients with untreated or recurrent brain tumours. The reduction in T2 relaxation times in the brain tumour patients was possibly caused by the accumulation of iron, since iron homeostasis is known to be altered in patients with tumours. We propose that increased iron deposition is a consequence of a higher risk of oxidative stress caused by an increased iron concentration in the plasma or cerebrospinal fluid.
Keywords: brain tumours; oxidative stress; iron; magnetic resonance imaging; basal ganglia